2015
DOI: 10.3389/fpsyg.2015.01363
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory model of emotional-cognitive variables in school mathematics performance: a longitudinal study in primary school

Abstract: This study tested a structural model of cognitive-emotional explanatory variables to explain performance in mathematics. The predictor variables assessed were related to students’ level of development of early mathematical competencies (EMCs), specifically, relational and numerical competencies, predisposition toward mathematics, and the level of logical intelligence in a population of primary school Chilean students (n = 634). This longitudinal study also included the academic performance of the students duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
0
11
0
4
Order By: Relevance
“…De acuerdo a los resultados de este estudio, hay evidencia suficiente para validar los objetivos de partida, pues del modelo se observa que la predisposición hacia las matemáticas resulta ser la variable con un mayor peso relativo en el rendimiento escolar en esta asignatura, lo que es coincidente con otros estudios que hacen hincapié en el rol modulador e incremental de las variables motivacionales a la hora de explicar el rendimiento académico cuando su efecto se modela junto a variables de tipo actitudinal o cognitivas (Cerda, et al, 2015;Jansen et al, 2013;Miñano y Castejón, 2011). La predisposición hacia las matemáticas, los esquemas de razonamiento formal y la inteligencia lógica explican un porcentaje importante de la variabilidad observada en el rendimiento escolar de los estudiantes en matemáticas, y de ellas la predisposición presenta un peso ponderado superior.…”
Section: Discusión Y Conclusionesunclassified
“…De acuerdo a los resultados de este estudio, hay evidencia suficiente para validar los objetivos de partida, pues del modelo se observa que la predisposición hacia las matemáticas resulta ser la variable con un mayor peso relativo en el rendimiento escolar en esta asignatura, lo que es coincidente con otros estudios que hacen hincapié en el rol modulador e incremental de las variables motivacionales a la hora de explicar el rendimiento académico cuando su efecto se modela junto a variables de tipo actitudinal o cognitivas (Cerda, et al, 2015;Jansen et al, 2013;Miñano y Castejón, 2011). La predisposición hacia las matemáticas, los esquemas de razonamiento formal y la inteligencia lógica explican un porcentaje importante de la variabilidad observada en el rendimiento escolar de los estudiantes en matemáticas, y de ellas la predisposición presenta un peso ponderado superior.…”
Section: Discusión Y Conclusionesunclassified
“…Socio-emotional abilities are variables that can influence academic performance, since it is observed that students present social, emotional, and behavioral difficulties that impact their ability to succeed in academic life (Loos-Sant 'Ana & Trancoso, 2014). For many years, one of the most investigated predictors of school success was intelligence, and, although its importance is recognized, other variables should be considered in this prediction, among which stand out socio-emotional abilities (Cerda et al, 2015). John and De Fruyt (2015) suggest that the model of the five major personality factors, known in the international literature as the Big Five, functions as an integrative model and organizer of socio-emotional abilities.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lot of diversity in the students according to what the level of mathematical competence is concerned. There are studies that indicate that these differences among students appear in Early Childhood Education and that basic competencies predict the performance in school some years later (Cerda, Pérez, Navarro, Aguilar, Casas, & Aragón, 2015;Morgan, Farkas, Aunio, Heiskari, Van Luit, &Vuorio, 2015, Jordan, Kaplan, Ramineni andWu, 2009). Currently, it is estimated that between 3 and 8% of primary school children have some Math Learning Difficulty (MLD) (González-Castro, Rodríguez, Cueli, Cabeza, & Álvarez, 2014).…”
Section: Introductionmentioning
confidence: 99%